Multipacting mitigation by atomic layer deposition: The case study of titanium nitride - Kalboussi, Y.; Dadouch, S.; Delatte, B.; Miserque, F.; Dragoe, D.; Eozenou, F.; Baudrier, M.; Tusseau-Nenez, S.; Zheng, Y.; Maurice, L.; Cenni, E.; Bertrand, Q.; et al. (Journal of applied physics, 2024)
This study investigates the use of atomic layer deposition (ALD) to mitigate multipacting phenomena inside superconducting radio frequency cavities used in particle accelerators while preserving high quality factors in the 1010 range. The unique ALD capability to control the film thickness down to the atomic level on arbitrary complex shape objects enables the fine-tuning of TiN film resistivity and total electron emission yield (TEEY) from coupons to devices. This level of control allows us to adequately choose a TiN film thickness that provides both high resistivity to prevent Ohmic losses and a low TEEY to mitigate multipacting for the application of interest. The methodology presented in this work can be scaled to other domains and devices subject to RF fields in vacuum and sensitive to multipacting or electron discharge processes with their own requirements in resistivities and TEEY values.